Tori Brunger: capstone - Brunger, Tori, artist (Colorado State University. Libraries, 2026)
The artist's statement: My name is Tori Brunger, and I am a Graphic Designer and Electronic artist. These stills are from my work in progress game, Storm the Castle, which is based on a dungeon crawler classic video game style and classic storyline of a knight in shining armor battling and slaying the dragon to rescue the princess trapped in a cage or dungeon cell. I find something so interesting about old timey games that are 2d and pixelated as these are the some of the types of games that I and many others grew up with and there is a sense of nostalgia and a longing for the simpler days of our youth. The concept for this game idea comes from junior year. I made a really rough draft of a dungeon crawler game with a knight going through a castle, avoiding booby traps, and fighting a dragon to save a princess. I would like to expand on this idea and maybe give it some more details such as different rooms and booby traps. I would also like to make the game a little more challenging as my first version of the game was simple and very easy to win. The final scene where you fight the dragon to save the princess will be much more challenging to finish.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art